Parenting dalam Perkembangan Anak Remaja di Lingkungan Keluarga (Studi Kasus: Pada Tim Dawis Mutiara Gading Kelurahan Sendangmulyo Kota Semarang) - Rohmansyah, Nur Azis (Fakultas Teknik, Universitas Bangka Belitung, 2023)
Parenting is how to educate parents to children, either directly or indirectly. The purpose of this Community Service (PKM) activity for parents who are members of the dawis team in Sendangmulyo Village, Semarang City is to increase understanding of parenting and its impact on children and adolescents as well as negative effects such as drug abuse, free sex and marriage early. The target to be achieved is to provide knowledge and skills regarding parents' understanding of parenting for children and adolescents as well as parents' understanding of the impact of parenting for children and adolescents in the Dawis Mutiara Gading Team, Sendangmulyo subdistrict, Semarang City optimally, through PKM activities for the Dawis Team . The method used is parenting and socialization. The output of this activity are: 1) Increased knowledge and insight of parents regarding parenting and its impact on children and adolescents. 2) Increased skills in caring for children and adolescents and being able to prevent as early as possible children and adolescents from falling into negative things such as drug abuse, free sex and early marriage. The conclusion from this PKM activity is the importance of the knowledge and skills of the parents of the dawis team members in raising, accompanying and educating families and children towards quality families. Creativity is needed in managing parenting, learning activities and sex education from an early age, especially in providing creative and innovative learning media.